Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18393/ejss.455128
|View full text |Cite
|
Sign up to set email alerts
|

Assessing soil quality issues for crop production function based on farmers’ perception: An experience from Itapaji Watershed in Southwestern Nigeria

Abstract: To successfully manage soil quality for sustainable crop production, there is need to identify issues affecting it. These are problems facing the capacity of soil to perform its functions and thus reducing its productivity. In addition, the similarities and differences between farmers' perception of soil quality issues and that of soil scientist are very pertinent. This study, which was carried out at Itapaji watershed in Ikole local government area of Ekiti state, aims at identifying soil quality issues using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…About that, Buthelezi-Dube et al (2019) revealed that local qualitative soil fertility knowledge of farmers links to crop performance and potentially supports laboratory soil analysis for smallholder agriculture in eastern South Africa. Adeyolanu et al (2018) showed also that farmers' perception of soil quality and soil scientists correlate well, i.e., farmers' perception identified compaction, erosion, low soil fertility as a result of low nutrient availability and retention, termite infestation, poor drainage, flooding, high land-use intensity without proper management and all these have the resultant effect of decreased crop yield or low productivity in Southwestern Nigeria.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…About that, Buthelezi-Dube et al (2019) revealed that local qualitative soil fertility knowledge of farmers links to crop performance and potentially supports laboratory soil analysis for smallholder agriculture in eastern South Africa. Adeyolanu et al (2018) showed also that farmers' perception of soil quality and soil scientists correlate well, i.e., farmers' perception identified compaction, erosion, low soil fertility as a result of low nutrient availability and retention, termite infestation, poor drainage, flooding, high land-use intensity without proper management and all these have the resultant effect of decreased crop yield or low productivity in Southwestern Nigeria.…”
Section: Introductionmentioning
confidence: 93%
“…reveal soil quality indicators mentioned by them were related to morphological (A horizon depth), chemical (organic matter and nutrient content), biological (presence of organisms), and physical (texture, bulk density, and porosity) attributes. In this direction, Adeyolanu et al (2018) observed that maize/cassava/yam farmers in Southwestern Nigeria identified soil quality through soil compaction, erosion, low drainage (physical attributes), low soil fertility (chemical attribute), and termite infestation (biological attribute). Lima et al (2013) reported that organic matter content, soil color, and edaphic fauna were the indicators most used by rice farmers in Southern Brazil to define soil quality in production areas.…”
Section: Soil Quality Status From Settled Farmers' Knowledgementioning
confidence: 99%